Graduate Student Unionization: A Unique American Issue? - Woldegiyorgis, Ayenachew A. (International Higher Education, 2018)
For over half a century, unionization of graduate students in US private institutions has remained a point of contention. Comparable practices elsewhere not only have a much longer history, but also offer alternatives in terms of form of organization, purpose, and type of membership.